Mechanobiology in the Comorbidities of Ehlers Danlos Syndrome - Royer, Shaina P.; Han, Sangyoon J. (Frontiers in Cell and Developmental Biology, 2022)
Ehlers-Danlos Syndromes (EDSs) are a group of connective tissue disorders, characterized by joint hypermobility and instability. Mechanically, various tissues from EDS patients exhibit lowered elasticity and lowered ultimate strength. This change in mechanics has been associated with EDS symptoms. However, recent evidence points toward a possibility that the comorbidities of EDS could be also associated with reduced tissue stiffness. In this review, we focus on mast cell activation syndrome and impaired wound healing, comorbidities associated with the classical type (cEDS) and the hypermobile type (hEDS), respectively, and discuss potential mechanobiological pathways involved in the comorbidities.